Du-Huo-Ji-Sheng-Tang and its active component Ligusticum chuanxiong promote osteogenic differentiation and decrease the aging process of human mesenchymal stem cells. (23rd February 2017) - Wang, Jir-You; Chen, Wei-Ming; Wen, Che-Sheng; Hung, Shih-Chieh; Chen, Pei-Wen; Chiu, Jen-Hwey
Abstract: Ethnopharmacological relevance: Postmenopausal osteoporosis is the most common bone disease worldwide. Information concerning the effects of herbal medicines on mesenchymal cell osteogenesis and senescence remains lacking. Aim of this study: This study was designed to investigate the effects of Du-Huo-Ji-Sheng-Tang (DHJST), a Chinese herbal medicine and its active component Ligusticum chuanxiong on osteogenic differentiation and the aging process of human mesenchymal cells (hMSCs). Materials & methods: hMSCs were used as in vitro model and osteogenesis was induced by administration of either osteogenesis inducing medium (OIM) or dexamethasone-depleted OIM (DDOIM) for 1-week or 2 weeks and the results were evaluated by measuring the formation of mineralization nodules. The effects of the compound recipe DHJST and its active component L. chuanxiong on hMSCs osteogenesis-related gene expression was determined by real-time PCR that targeted bone morphogenetic protein-2 ( BMP2 ), RUNX2, ALP, COL-1, osteopontin ( OPN ), and osteocalcin ( OCN ). Antibodies against BMP-related signaling pathway proteins, such as BMP-2, ERK, SMAD 1/5/8, and RUNX2, were also detected at the protein level by Western blotting. Finally, the cumulative growth curve and senescence of the hMSCs were evaluated in order to assess the aging process. Results: L. chuanxiong increased osteogenic activity in hMSCs and up-regulated BMP-2 and RUNX2 gene expression via the activation of SMAD 1/5/8 and ERK signaling. Furthermore DHJST also showed a trend towards promoting the same effects in the same system. In the absence of dexamethasone, DHJST did activate SMAD 1/5/8 and ERK signaling and hence increased RUNX2 protein expression in hMSCs. In addition, both DHJST and L. chuanxiong delayed the hMSCs aging process by decreasing cell senescence. Conclusions: We concluded that DHJST and its active component L. chuanxiong are able to promote osteogenic activity and decrease hMSCs senescence as cells age. Graphical abstract: